Disturbed Sleep in PTSD: Thinking Beyond Nightmares - Lancel, Marike; van Marle, Hein J. F.; Van Veen, Maaike M.; van Schagen, Annette M. (Frontiers in Psychiatry, 2021)
Sleep disturbances frequently co-occur with posttraumatic stress disorder (PTSD). Insomnia and nightmares are viewed as core symptoms of PTSD. Yet, relations between disturbed sleep and PTSD are far more complex: PTSD is linked to a broad range of sleep disorders and disturbed sleep markedly affects PTSD-outcome. This article provides a concise overview of the literature on prevalent comorbid sleep disorders, their reciprocal relation with PTSD and possible underlying neurophysiological mechanisms. Furthermore, diagnostic procedures, standard interventions - particularly first choice non-pharmacological therapies - and practical problems that often arise in the assessment and treatment of sleep disturbances in PTSD are described. Finally, we will present some perspectives on future multidisciplinary clinical and experimental research to develop new, more effective sleep therapies to improve both sleep and PTSD.